2015
DOI: 10.1007/s00203-015-1126-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel antimicrobial peptide specifically active against Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis, the major etiologic agent of chronic periodontitis, produces a broad spectrum of virulence factors, including outer membrane vesicles, lipopolysaccharides, hemolysins and proteinases. Antimicrobial peptides (AMPs) including bacteriocins have been found to inhibit the growth of P. gingivalis; however, these peptides are relatively large molecules. Hence, it is difficult to synthesize them by a scale-up production. Therefore, this study aimed to synthesize a shorter AMP that was still a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…So far, scholars have confirmed the antibacterial effect of many natural and synthetic AMPs, including Bac8c, Aedesin, decapeptide, XLAsp-P1, LL-37 and variant, Pep-7, and HBD3-C15 [35,87,[110][111][112][113][114][115][116], which provided us with the study methods of this new AMP GERM CLEAN. What's more exciting, Wang et al [43,117] in our hospital successfully synthesized three new AMPs (GH8, GH12, and GH16) and further studied the bacteriostatic properties and mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…So far, scholars have confirmed the antibacterial effect of many natural and synthetic AMPs, including Bac8c, Aedesin, decapeptide, XLAsp-P1, LL-37 and variant, Pep-7, and HBD3-C15 [35,87,[110][111][112][113][114][115][116], which provided us with the study methods of this new AMP GERM CLEAN. What's more exciting, Wang et al [43,117] in our hospital successfully synthesized three new AMPs (GH8, GH12, and GH16) and further studied the bacteriostatic properties and mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, two studies have previously identified antibacterial peptides specifically targeting P . gingivalis (Franzman et al, ; Suwandecha, Srichana, Balekar, Nakpheng, & Pangsomboon, ). In addition to their therapeutic effect, target‐specific antibacterials may be used as a tool to study the role of a particular pathogen in complex microbial communities such as biofilms found in the oral cavity (Frias‐Lopez, ; Guo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the oral cavity, different studies have published promising results on antimicrobial peptides specifically designed to target S. mutans, a key pathogen involved in caries (Eckert et al, 2006;Guo et al, 2015;Mai et al, 2011). Furthermore, two studies have previously identified antibacterial peptides specifically targeting P. gingivalis (Franzman et al, 2009;Suwandecha, Srichana, Balekar, Nakpheng, & Pangsomboon, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a study where 236 lactic acid bacterial isolates from food were included, none of the tested strains was able to affect the growth of gram-negative periodontal pathogens, including P. gingivalis [ 42 ]. Antimicrobial agents from L. paracasei HL32 have been shown to suppress P. gingivalis growth [ 43 , 44 ], and a short biosynthetic peptide, Pep-7, was produced and demonstrated to be selectively active against P. gingivalis [ 45 ]. We show that the antimicrobial effect of the two-peptide bacteriocin PLNC8 αβ occur rapidly and is very efficient, using liposomes and viable P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%